Genetic risk, adherence to a healthy lifestyle, and type 2 diabetes risk among 550, 000 Chinese adults: results from 2 independent Asian cohorts. Issue 3 (24th January 2020) - Li, Haoxin; Khor, Chiea-Chuen; Fan, Junning; Lv, Jun; Yu, Canqing; Guo, Yu; Bian, Zheng; Yang, Ling; Millwood, Iona Y; Walters, Robin G; Chen, Yiping; Yuan, Jian-Min; et al.
ABSTRACT: Background: Whether genetic susceptibility to type 2 diabetes is modified by a healthy lifestyle among Chinese remains unknown. Objectives: The aim of the study was to determine whether genetic risk and adherence to a healthy lifestyle contribute independently to the risk of developing type 2 diabetes. Methods: We defined a lifestyle score using BMI, alcohol intake, smoking, physical activities, and diets in 461, 030 participants from the China Kadoorie Biobank and 38, 434 participants from the Singapore Chinese Health Study. A genetic risk score was constructed based on type 2 diabetes loci among 100, 175 and 16, 172 participants in each cohort, respectively. A Cox proportional-hazards model was used to estimate the interaction between genetic and lifestyle factors on the risk of type 2 diabetes. Results: In 2 independent Asian cohorts, we consistently found a healthy lifestyle (the bottom quintile of lifestyle score) was associated with a substantially lower risk of type 2 diabetes than an unhealthy lifestyle (the top quintile of lifestyle score) regardless of genetic risk. In those at a high genetic risk, the risk of type 2 diabetes was 57% lower among participants with a healthy lifestyle than among those with an unhealthy lifestyle in the pooled cohorts. Among participants at high genetic risk, the standardized 10-y incidence of type 2 diabetes was 7.11% in those with an unhealthy lifestyle vs. 2.45% in those with a healthy lifestyle. Conclusions: In 2 independent cohorts involving 558, 302 Chinese participants, we did not observe an interaction between genetics and lifestyle with type 2 diabetes risk, but our findings provide replicable evidence to show lifestyle factors and genetic factors were independently associated with the risk of type 2 diabetes. Within any genetic risk category, a healthy lifestyle was associated with a significantly lower risk of type 2 diabetes among the Chinese population.